The Effect Of The Textual Structure Strategy On Reading Comprehension Among Fourth-Grade Literary Students (Journal of the College of Basic Education, 2024)
The current research aims to identify (the impact of the strategy of textual structures on reading comprehension in fourth grade literary students)The researcher followed the experimental curriculum, being the appropriate curriculum and appropriate to the nature of her research and its purpose, and the researcher identified the current research community with students of the literary fourth grade in secondary and day preparatory schools for girls affiliated to the Directorate of education of Baghdad/ Al-Karkh I in Baghdad governorate for the academic year (2023-2024), and the researcher chose her research sample by random method, consisting of (60) students at Al-Bayan high school for girls, affiliated to the Directorate of education of Baghdad/ al-Rusafa I, and they were randomly distributed to two groups (experimental and control), for (30) per set.The researcher studied the same two research groups, starting on Sunday 2023/ 10/ 8 the experiment ended on Monday, corresponding to(2024/1/11), with one class per week for each group, and the experiment lasted one semester the first semester, and the researcher prepared a test to measure reading comprehension consisting of (31) paragraph divided into objective questions and essays applied to the experimental and Control Research Groups at the end of the experiment, the test was characterized by honesty, consistency and objectivity, and the researcher processed the research data and results using the statistical bag (SPSS) using the following equations :Mann, Tenney test and Samira test Nof, coefficient of difficulty, coefficient of discrimination, effectiveness of alternatives and the kider equation- Richardsonادلة and the Cooper equation and the alpha-krohnbach equation, and the research has yielded the following results : the female students of the experimental group outperformed the female students of the control group .